PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP KINERJA LEMBAGA PERKREDITAN DESA (LPD) SERTA DAMPAKNYA BAGI LOYALITAS MASYARAKAT DESA (STUDI PADA LPD DI KABUPATEN BADUNG BALI) - I Gusti Ngurah Putra Suryanata (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
This research aims to examine the effect of external and internal factors on the performance of Village Credit Union – Lembaga Perkreditan Desa (hereinafter referred to as LPD) and village community loyalty in Badung Regency, Bali. The performance of LPD that has been measured based on financial approaches only, will be studied more deeply through several more approaches such as customer or village community satisfaction, internal business process, and growth and learning that is known as balanced scorecard measurement concept. This research is conducted in Badung Regency and using purposive sampling as sampling technique. Thera are 64 LPD out of 119 LPD that is chosen as the research sample. It was based on the consideration that the LPD which was established before 1997, which was the beginning of the year of the economic crisis experienced by Indonesia and the condition of the LPD in the crisis years still existed, while many similar financial institutions collapsed. Data analysis is conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. Theoretical findings of the study reveal that external factors with indicators of local regulations, awig-awig, economic conditions, competition from similar financial institutions have a significant positive effect on LPD performance; Internal factors with indicators of organizational structure, culture, human resources have a significant positive effect on LPD performance; External factors have a significant positive effect on internal LPD factors.